2018
DOI: 10.1002/humu.23550
|View full text |Cite
|
Sign up to set email alerts
|

De novo variants in RHOBTB2 , an atypical Rho GTPase gene, cause epileptic encephalopathy

Abstract: By whole exome sequencing, we identified three de novo RHOBTB2 variants in three patients with epileptic encephalopathies (EEs). Interestingly, all three patients showed acute encephalopathy (febrile status epilepticus), with magnetic resonance imaging revealing hemisphere swelling or reduced diffusion in various brain regions. RHOBTB2 encodes Rho-related BTB domain-containing protein 2, an atypical Rho GTPase that is a substrate-specific adaptor or itself is a substrate for the Cullin-3 (CUL3)-based ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…RHOBTB2 (Chr 8:22,987,250-23,020,198, MIM: 607352) Heterozygous missense variants in Rho-related BTB domaincontaining protein 2 (RHOBTB2) were reported in 2018 in 13 individuals with DEEs (102, 103). In the initial reports, 11/13 had a movement disorder (dystonia, dyskinesia, chorea and stereotypies), described as paroxysmal in 4/11 (paroxysmal dyskinesia, dystonic-athetoid attacks) (5,38,103). Subsequently, two case reports focusing on the PxMDs have been published, including a patient with paroxysmal dyskinesia and developmental delay without epilepsy (38,39).…”
Section: Predominant Dyskinesia Genesmentioning
confidence: 99%
“…RHOBTB2 (Chr 8:22,987,250-23,020,198, MIM: 607352) Heterozygous missense variants in Rho-related BTB domaincontaining protein 2 (RHOBTB2) were reported in 2018 in 13 individuals with DEEs (102, 103). In the initial reports, 11/13 had a movement disorder (dystonia, dyskinesia, chorea and stereotypies), described as paroxysmal in 4/11 (paroxysmal dyskinesia, dystonic-athetoid attacks) (5,38,103). Subsequently, two case reports focusing on the PxMDs have been published, including a patient with paroxysmal dyskinesia and developmental delay without epilepsy (38,39).…”
Section: Predominant Dyskinesia Genesmentioning
confidence: 99%
“…Three children with a RHOBTB2 mutation were identified in a cohort of 1,230 children with infantile or early-childhood epilepsy. 2 It has been found that the altered protein RHOBTB2 is relatively resistant to degradation, leading to overexpression of the altered protein. In Drosophila, overexpression of the ortholog RhoBTB is associated with seizure susceptibility and severe locomotor defects.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that children with a RHOBTB2 mutation do not show stable intellectual impairment, and several show regression-or stagnation-associated with the occurrence of seizures or acute encephalopathy. 1,2,9 When the seizures occur at young age, this regression or stagnation is possibly not recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less common diseases and conditions that one may find in a neurocritical care unit are doubly disadvantaged, as even larger sample sizes are required for sequencing analyses than GWAS, due to the need for many observations to identify rare exonic or intronic variants associated with disease (17,36). As pricing models improve and larger and larger community or hospital-based cohorts receive sequencing through clinical or biobanking efforts, it is hoped that even uncommon conditions such as subarachnoid hemorrhage or status epilepticus will benefit from the insights achievable through sequencing analysis, where case/control and smaller sequencing studies have shown promise (37,38).…”
Section: Post-gwas Eramentioning
confidence: 99%